KESIMETRISAN DALAM SISTEM DEMONSTRATIVA BAHASA MANDAILING - Namsyah Hot Hasibuan (LITERA, 2015)
AbstractThis study aims to describe the demonstrative system in the Mandailing language.The data were collected from native speakers in their daily communication. They wereanalyzed by classifying demonstrative expressions based on Levinson’s theory and theiruses were described in accordance with field observations and informants’ explanation.The results of the study are as follows. First, there are three types of relative distancesfor object reference. The object reference in the three types of relative distances uses aparticular demonstrative expression. Second, a demonstrative expression for each relativedistance has the same base. This shows that there is a symmetric relationship amongdemonstrative expressions. The object relatively close to the speaker is referred to by ademonstrative expression using the element on. The object relatively distant from thespeaker but it is close to the addressee is referred to by a demonstrative expression usingthe element i. The object relatively distant from the speaker and the addressee is referredto by a demonstrative expression using the element odu.